The Influence of Transformational Leadership Style and Job Mutations on Employee Performance at BPJS Employment - Faradillah Faradillah; Marlina Widiyanti; Muhammad Yusuf; Mohammad Adam (Journal of Social Science, 2023)
This research was conducted with the aim of determining the influence of transformational leadership style and job transfers on employee performance at BPJS Employment. The population in this study is all permanent employees of BPJS Employment, South Sumatra regional office in 2022-2023, totaling 100 employees. In this research, the respondents in this research are all 100 permanent employees at BPJS Employment in 2022-2023 and all of them are the number of respondents in this research using the census technique method. The results of multiple linear analysis show that transformational leadership style and job transfer have a positive and significant effect on employee performance. Transformational leadership style has a dominant influence on employee performance. Transformational leadership style, it is expected that the role of superiors needs to be an evaluation. Superiors are expected to provide enthusiasm and appreciation for employee performance results by giving awards to employees who provide good performance results and achieve achievements. Job transfers, it is hoped that the process for carrying out this rotation will need to be adjusted again. Where, if employees are often given work rotation, employees have to change their work environment and living environment.